Performa Saham Sektor Energi selama Periode Covid-19 Delta dan Omicron di Indonesia - Firnanda, Annisa; Budiasih, Budiasih (Politeknik Statistika STIS, 2023)
In production activities, energy companies need sufficient funds, one of which is by issuing stocks. Before investing, investors pay attention to the rate of return and risk, such as financial losses. In addition, the volume of stock trading is also used to assess the performance of a stock. The Covid-19 pandemic affects the risk of stocks in the world's energy sector, including Indonesia. The news about Covid-19 that mutated gave rise to investor panic, so that the volatility (risk) of stocks increased. This study aims to identify the existence of stock risk and the relationship between stock risk with the volume of energy trading in the energy sector in the Covid-19 period of the Delta and Omicron variants. The results showed that the risk of the energy sector shares was identified in the Delta period. The risk of the energy sector is quite stable, and suitable for risk aversion. It was also obtained that there was a positive relationship between stock risk and the volume of stock trading in the energy sector in the Delta period where the increase or decrease in the volume of stock trading, was followed by an increase or decrease in the risk of the energy sector stocks.